Mass Spectrometry Imaging of Bio‐oligomer Polydispersity in Plant Tissues by Laser Desorption Ionization from Silicon Nanopost Arrays. Issue 16 (9th March 2021) - Samarah, Laith Z.; Tran, Tina H.; Stacey, Gary; Vertes, Akos
Abstract: Mass spectrometry imaging (MSI) enables simultaneous spatial mapping for diverse molecules in biological tissues. Matrix‐assisted laser desorption ionization (MALDI) mass spectrometry (MS) has been a mainstream MSI method for a wide range of biomolecules. However, MALDI‐MSI of biological homopolymers used for energy storage and molecular feedstock is limited by, e.g., preferential ionization for certain molecular classes. Matrix‐free nanophotonic ionization from silicon nanopost arrays (NAPAs) is an emerging laser desorption ionization (LDI) platform with ultra‐trace sensitivity and molecular imaging capabilities. Here, we show complementary analysis and MSI of polyhydroxybutyric acid (PHB), polyglutamic acid (PGA), and polysaccharide oligomers in soybean root nodule sections by NAPA‐LDI and MALDI. For PHB, number and weight average molar mass, polydispersity, and oligomer size distributions across the tissue section and in regions of interest were characterized by NAPA‐LDI‐MSI. Abstract : Simultaneous chemical analysis and spatial mapping of homopolymers used for energy storage and molecular feedstock in biological tissues are challenging using conventional MS imaging. Here, the spatial and size distributions for oligomers from polyhydroxybutyrate, polysaccharide, and polyglutamic acid are profiled in rhizobia‐infected soybean root nodules by MS imaging using nanophotonic ionization from silicon nanopost arrays and MALDI.